THE HEGEMONY OF ENGLISHFOUND IN POSTS ON FACEBOOK COMMUNITIES OF INDONESIAN ANDROID SMARTPHONE USERS - Guswandi Guswandi; Jufrizal Jufrizal; Fitrawati Fitrawati (English Language and Literature, 2017)
This research aimed at finding out forms of language hegemony of English and factors motivating language hegemony of English into Bahasa Indonesia found in posts on Facebook communities of Indonesian android smartphone users. The method used in this research was descriptive. The data of the research were texts of 150 posts obtained from 10 Facebook groups. In other words, the research data consisted of 150 texts. Out of 150 texts, it was found 244 frequencies of forms of language hegemony of English and 220 frequencies of factors motivating language hegemony of English into Bahasa Indonesia. The results showed that forms of language hegemony of English were: borrowing as the most dominant form, language interference, code mixing, and code switching. It indicated that the hegemony in this case occured in integrating of the two languages rather than totally dominating in which it was only the language of dominant group was used. Meanwhile, factors motivating language hegemony of English found were social interaction as the most influencing one and socio-cultural change.